Current Susceptibility Surveillance and Distribution of Antimicrobial Resistance in N. gonorrheae within WHO Regions - Marina Radovanovic; Dusan Kekic; Milos Jovicevic; Jovana Kabic; Ina Gajic; Natasa Opavski; Lazar Ranin (Pathogens, 2022)
Neisseria gonorrhoeae (N. gonorrhoeae) is the etiological agent of the second most common sexually transmitted disease in the world, gonorrhoea. Currently recommended and last available first-line therapy is extended-spectrum cephalosporins most often combined with azitromycin. However, misuse of antibiotics and the abilities of N. gonorrhoeae to acquire new genetic and plasmid-borne resistance determinants has gradually led to the situation where this bacterium has become resistant to all major classes of antibiotics. Together with a generally slow update of treatment guidelines globally, as well as with the high capacity of gonococci to develop and retain AMR, this may lead to the global worsening of gonococcal AMR. Since effective vaccines are unavailable, the management of gonorrhoea relies mostly on prevention and accurate diagnosis, together with antimicrobial treatment. The study overviews the latest results of mostly WHO-initiated studies, primarily focusing on the data regarding the molecular basis of the resistance to the current and novel most promising antibacterial agents, which could serve to establish or reinforce the continual, quality-assured and comparable AMR surveillance, including systematic monitoring and treatment with the use of molecular AMR prediction methods.